A Simple Flow Classification Parameter Can Discriminate Rupture Status in Intracranial Aneurysms. Issue 5 (18th May 2020) - Asgharzadeh, Hafez; Shahmohammadi, Ali; Varble, Nicole; Levy, Elad I; Meng, Hui; Borazjani, Iman
Abstract: BACKGROUND: A simple dimensionless aneurysm number ($An$ ), which depends on geometry and flow pulsatility, was previously shown to distinguish the flow mode in intracranial aneurysms (IA): vortex mode with a dynamic vortex formation/evolution if $An > 1$, and cavity mode with a steady shear layer if $An < 1$ . OBJECTIVE: To hypothesize that $An\ > \ 1$ can distinguish rupture status because vortex mode is associated with high oscillatory shear index, which, in turn, is statistically associated with rupture. METHODS: The above hypothesis is tested on a retrospective, consecutively collected database of 204 patient-specific IAs. The first 119 cases are assigned to training and the remainder to testing dataset. $An$ is calculated based on the pulsatility index ( PI ) approximated either from the literature or solving an optimization problem (denoted as$\ \widehat {PI}$ ). Student's t -test and logistic regression (LR) are used for hypothesis testing and data fitting, respectively. RESULTS: $An$ can significantly discriminate ruptured and unruptured status with 95% confidence level ( P < .0001). $An$ (using PI ) and $\widehat {An}$ (using $\widehat {PI}$ ) significantly predict the ruptured IAs (for training dataset $An\!:\ $ AUC = 0.85, $\widehat {An}\!:\ $ AUC = 0.90, and for testing dataset $An\!:\ $ sensitivity = 94%, specificity = 33%, $\widehat {An}\!:\ $ sensitivity = 93.1%, specificity = 52.85%). CONCLUSION: $An > 1$ predicts ruptured status. Unlike traditional hemodynamic parameters such as wall shear stress and oscillatory shear index, $An$ has a physical threshold of one (does not depend on statistical analysis) and does not require time-consuming flow simulations. Therefore, $An$ is a simple, practical discriminator of IA rupture status.